(untitled) (Computer Aided Drug Development, 2024)
Author Prof. Ashish Rathi Associate Professor, Dept of Pharmaceutical Chemistry, Dr. Rajendra Gode College of Pharmacy, Malkapur, Maharashtra, India Abstract Computational modeling of drug disposition represents a critical approach in modern pharmaceutical development, utilizing mathematical and computational techniques to predict how drugs behave within biological systems. These models integrate physicochemical properties, physiological parameters, and mathematical algorithms to simulate drug absorption, distribution, and excretion processes. Various modeling techniques, from empirical to mechanistic approaches, enable scientists to predict drug solubility, intestinal permeation, tissue distribution, and elimination patterns. The integration of in silico methods with experimental data has revolutionized our ability to understand and optimize drug disposition characteristics early in development, reducing the need for extensive experimental testing. Advanced computational tools now allow for accurate predictions of drug-specific parameters, including absorption rates, distribution patterns, and excretion profiles, facilitating more efficient drug development processes and improved therapeutic outcomes. This systematic approach to modeling drug disposition has become indispensable in pharmaceutical research, supporting decision-making processes and accelerating the development of new therapeutic agents. Keywords: Computational modeling; Drug disposition; ADME prediction; Physiological modeling; Solubility prediction; Intestinal absorption; Distribution models View PDF